Training to change practice : behavioural science to develop effective health professional education - Hart, Jo; Byrne-Davis, Lucie; Maltinsky, Wendy; Bull, Eleanor, 1987- (Hoboken, NJ : John Wiley & Sons Ltd., 2023)
"Continuing professional development (CPD) is an umbrella term, covering all kinds of activities that help health professionals learn and develop throughout their careers (e.g., Peck et al. 2000, HCPC 2015). Among the most widespread CPD activities are the structured education opportunities that we will describe in this book as CPD training courses, although also called educational meetings or workshops (Forsetlund et al. 2021) As long ago as 2002, the UK NHS was estimated to directly spend approximately £1 billion annually on workforce CPD (Brown et al. 2002). CPD is seen as crucial to developing the more flexible, multidisciplinary health workforce envisioned in the recent NHS Long Term plan (Karas et al. 2020). Given how much is invested in CPD, it is even more important that CPD is designed in such a way as to maximise practice improvement, so that the benefits of all this investment can be fully realised in terms of improving care delivery and ultimately health outcomes"--
Keywords: Medicine -- Study and teaching (Continuing education) -- Great Britain; Medical personnel -- Training of -- Great Britain; Medicine -- Practice -- Great Britain; Electronic books